Rent Sharing and Inclusive Growth - Brian Bell; Pawel Bukowski; Stephen Machin (Institute of Labor Economics (IZA), 2018)
The long-run evolution of rent sharing is empirically studied. Based upon a comprehensive and harmonized panel of the top 300 publicly quoted British companies over thirty five years, the paper reports evidence of a significant fall over time in the extent to which firms share rents with workers. It confirms that companies do share their profits with employees, but at much smaller scale today than they did during the 1980s and 1990s. This is a robust finding, corroborated with industry-level analysis for the US and EU. The decline in rent sharing is coincident with the rise of product market power that has occurred as worker bargaining power has dropped. Although firms with more market power previously shared more of their profits, they experienced a stronger fall in rent sharing after 2000.
Keywords: J30; 330; rent sharing; inclusive growth